The effects of the functional levels of children with cerebral palsy on the quality of life of caregivers - Dogruoz Karatekin, Bilinc; Icagasioglu, Afitap (Journal of Surgery and Medicine, 2022)
Background/Aim: Psychological status and quality of life of caregivers with children with cerebral palsy are lower than the population. The functional status of the child is one of the factors affecting the caregiver's quality of life. However, the relationship between gross motor and hand functions, communication, oromotor skills, oropharyngeal functions and the caregiver's quality of life remains unclear. The aim of the study is to examine the effects of the functional levels of children with cerebral palsy on the quality of life of their caregivers. Methods: Two hundred and seventeen children with cerebral palsy and their caregivers were included in this cross-sectional study. Inclusion criteria were; (i) Children aged 0-18, diagnosed with cerebral palsy (CP), followed in the pediatric rehabilitation outpatient clinic of the university, (ii) individuals who care for children with CP and volunteer to participate in the study, (iii) individuals who have a literacy level of understanding the purpose of the study and the forms to be filled in. Children's demographic information (age, gender), cerebral palsy types were recorded and detailed functional evaluation was made. The identity of the caregiver was recorded and quality of life was evaluated with the Short Form-12 (SF-12). Functional classification of the children were evaluated with Gross Motor Function Classification System (GMFCS), Manual Ability Classification System (MACS), Communication Function Classification System (CFCS) and Eating and Drinking Ability Classification System (EDACS). The relationship between the child's functional level in each scale and the caregiver's SF-12 score was investigated. Results: Of the 117 children with a mean age of 7.62 (4.08), 52.5% were male (n=114) and 47.5% (n=103) female. According to CP types, 89.3% were spastic (n=191) (78.1% of them bilateral, 21.9% unilateral), 5.6% ataxic (n=12) and 5.1% dyskinetic (n=11). Median SF-12 PCS and MCS were 51.69 (25.76-62.92) and 55.36 (26.64-60.69), respectively. When the SF-12 scores were evaluated according to the functional levels of the children, both SF-12 PCS and SF-12 MCS scores differed significantly according to the GMFCS, MACS, CFCS and EDACS levels (P<0.01). Conclusion: The caregiver's quality of life is related to the gross motor and hand functions, oropharyngeal functions, communication and oromotor skills of the children with cerebral palsy. Therefore, comprehensive functional evaluation of children with cerebral palsy is important.